Cetylpyridinium chloride at sublethal levels increases the susceptibility of rat thymic lymphocytes to oxidative stress. (March 2017) - Imai, Hiroto; Kita, Fumiya; Ikesugi, Sho; Abe, Masami; Sogabe, Shizuka; Nishimura-Danjobara, Yumiko; Miura, Hajime; Oyama, Yasuo
Abstract: Cetylpyridinium chloride (CPC) is an antimicrobial agent used in many personal care products, with subsequent release into the environment. Since CPC is found at low concentrations in river and municipal wastewater, its influence on wildlife is of concern. Therefore, in this study, we used flow cytometry to examine the effects of sublethal concentrations of CPC on rat thymic lymphocytes in order to characterize the cellular actions of CPC at low concentrations in the presence and absence of H2 O2 -induced oxidative stress. CPC treatment increased the population of living cells with phosphatidylserine exposed on the outer surface of their plasma membranes (a marker of early stage apoptosis), elevated intracellular Zn 2+ levels, and decreased the cellular content of nonprotein thiols. CPC also potentiated the cytotoxicity of H2 O2 . Our results suggest that, even at environmentally relevant sublethal concentrations, CPC exerts cytotoxic effects under oxidative stress conditions by increasing intracellular Zn 2+ concentration and decreasing the cellular content of nonprotein thiols. These findings indicate that, under some in vitro conditions, CPC is bioactive at environmentally relevant concentrations. Therefore, CPC release from personal care products into the environment may need to be regulated to avoid its adverse effects on wildlife. Highlights: Cetylpyridinium chloride (CPC) is an antimicrobial agent used in personal care products. CPC is subsequently released into the environment. Sublethal levels of CPC modified cellular parameters in rat thymocytes. CPC exerted profound cytotoxic action on the cells under oxidative stress. Environmentally-relevant levels of CPC is suggested to be bioactive under certain conditions.